Frailty, and not medicines with anticholinergic or sedative effects, predicts adverse outcomes in octogenarians admitted for myocardial infarction: Population‐level study. (7th December 2020) - Lopez, Derrick; Preen, David B.; Etherton‐Beer, Christopher; Sanfilippo, Frank M.
Abstract: Objective: To determine independent associations between the use of medicines with anticholinergic or sedative effects and frailty with outcomes of length of stay (LOS), coronary artery procedure performed and 30‐day deaths in octogenarians admitted for a myocardial infarction (MI). Methods: We quantified patient exposure to medicines with anticholinergic or sedative effects using the drug burden index (DBI) and frailty using the hospital frailty risk score (HFRS). We used multivariable regression methods to determine the association between DBI and HFRS with outcomes of LOS, coronary artery procedures performed and 30‐day deaths. Results: HFRS and not DBI score was significantly associated with receipt of coronary artery procedures (odds ratio [OR] 0.42; 95% CI 0.28‐0.62 for high‐ versus low‐risk groups) and 30‐day deaths (OR 1.58; 95% CI 1.12‐2.24 for high‐ versus low‐risk groups). Conclusion: Frailty risk is a more important predictor of outcomes than DBI score for octogenarians with an MI.